TRAINING THE COMPETITIVE GRADUATES OF PEDAGOGICAL HIGHER SCHOOLS VIA THE SYSTEM OF ADDITIONAL EDUCATION - L. A. Amirova; Y. A. Fedorova (Образование и наука)
The paper is devoted to the problem of professional selfdetermination, which involves selection of and enrolment in a particular educational institution, as well as preparation for a job placement after graduation in the fast changing labor market. Additionally, the authors point out the related complications, caused by deformations in the professional orientation system, and leading to a professional self-identification crisis. The aim of the research is to demonstrate that fostering the competitive university graduates -the priority task of the modern higher school - requires psycho-pedagogical facilitation, and flexible alternative application of available resources of time, content, organization, and technology. However, the necessity to follow the Federal State Educational Standards and other regulatory procedures slows down the higher school’s response to changing realities, and hinders the prompt development of mobile and adaptive educational programs. As an effective tool for solving the problem of professional selfidentification, the author recommends the variational programs of additional education, regarded as an option to the major specialization. The paper discusses the “SchoolofProfessional Success” project, approbated inBashkirskyStatePedagogicalUniversity, based on the competence and person-oriented approaches, and analytical monitoring of students’ requirements for additional skills and knowledge. The above experience can be further extrapolated to different fields of training.